2014
DOI: 10.1111/inr.12120
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with birth weight inequalities in Jordan

Abstract: The findings inform our understanding of some social factors affecting birth weights of neonates in Jordan and development of effective public health interventions that could reduce the adverse effects of such factors on newborn birth weight. Preconception and antenatal care is also important for early detection of such possible risk and targeting mothers who require early interventions and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 29 publications
4
29
1
7
Order By: Relevance
“…Maternal underweight was another significant factor involved [24]. Maternal nutritional status has also an important role to play in birth weight of infants [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal underweight was another significant factor involved [24]. Maternal nutritional status has also an important role to play in birth weight of infants [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Low level of household wealth is also a background characteristic contributing to the prevalence of undernourished children (13,(15)(16)(17)(18) . While low household income has a negative effect on children's nutritional status, education acts as a protective factor following the pattern that children whose mothers have higher or high education are more likely to be well-nourished Some studies have confirmed that mother's education is one of the main determinants of undernutrition (12)(13)(14) . Also, it has been shown that children whose mother was more educated were more likely to consume the optimal amounts of protein, Ca and vitamins necessary for their proper physical and psychological growth (19) .…”
mentioning
confidence: 99%
“…The observed rate (18.1%) is similar to that reported recently in Baghdad 3, 4 . This rate is higher than in the neighbor countries 5,6 . This finding reflects the high LBW in Iraq.…”
mentioning
confidence: 61%